KORELASI KEMAMPUAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS PARAGRAF ARGUMENTASI SISWA KELAS VIII.1 SMP NEGERI 7 BUKITTINGGI - Delfianto Delfianto (STKIP ROKANIA, 2017)
The purpose of this study is to describe the relationship of reading comprehension skills with the ability to write paragaraf argumentation of students of grade VIII.1 SMP N 7 Bukittinggi. This type of research is classified as quantitative research using correction method. The sample in this study is the students of gradeVIII.1 SMP N 7 Bukittinggi registered in the academic year 2016/2017 as many as 29 students. Data collection is done through comprehension reading tests and the ability to write paragraphs of argumentation. Based on the results of research, showed the existence of a significant relationship between the ability to read comprehension by writing argumentation with r calculate the correlation of 0.976 with sigma 0.000 greater than r table 0.470 at the level of α 0.01. With the sense that there is a significant relationship between reading ability and writing skills. With its determinant coefficient of 0.952. It can be understood that r square of 0.952 can be KP of 95.2%. This means that the ability to read comprehension helps the development of students' ability to write argumentation and about 5% assisted by other factors, can take the form of motivation or perseverance.